2015
DOI: 10.1039/c5ra22623f
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel synthesis of ZrO2–SiO2 catalysts for the transformation of bioethanol and acetaldehyde into 1,3-butadiene

Abstract: The sol-gel synthesized catalysts showed significantly higher selectivity for 1,3-butadiene (69.7%), at a high WHSV of 1.8 h−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The former studies conducted by other researchers showed a possibility of industrial application of Zr-Si catalytic system in ethanol conversion to BD process. In our previous work, 16 we reported the application of sol-gel ZrO 2 -SiO 2 catalysts and gained a relatively high performance compared with the results in other references. Meanwhile, the selectivity to dehydration products remains high and the catalysts show a relatively poor durability on the long-time stability test.…”
Section: Introductionmentioning
confidence: 90%
“…The former studies conducted by other researchers showed a possibility of industrial application of Zr-Si catalytic system in ethanol conversion to BD process. In our previous work, 16 we reported the application of sol-gel ZrO 2 -SiO 2 catalysts and gained a relatively high performance compared with the results in other references. Meanwhile, the selectivity to dehydration products remains high and the catalysts show a relatively poor durability on the long-time stability test.…”
Section: Introductionmentioning
confidence: 90%
“…[18,22,23,31] Due to this, it has been reported different optimum Mg-to-Si molar ratios for 1,3-BD formation, depending on the synthesis procedure employed. [13,18,23] Among the catalyst preparation procedures, different methods have been investigated such as physical mixtures of MgO and SiO2, [11,13] wet-kneading, [10][11][12][13]22,23] sol-gel, [18,24] impregnation [13] and co-precipitation. [22,25,26] Whereas it has been proven that a physical mixture between precursor oxides is not suitable for 1,3-BD formation, since resultant catalysts show similar features to single MgO and SiO2 phases, wet-kneading methods have been the most widely discussed in the literature with less attention being dedicated to sol-gel and co-precipitation methods.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was studied also over ZrO 2 /SiO 2 and Ta 2 O 5 /SiO 2 catalysts. [7,8]. At a somewhat higher AL content of the feed the molar conversion of the AL/EL mixture was near to 30-40 %, whereas the BD yield was also about 20-30 %.…”
Section: Introductionmentioning
confidence: 79%
“…Several studies revealed [6,7] that higher yield of BD was obtained from a feed of AL/EL mixture than from pure EL. Therefore, there is an obvious interest to get AL from the readily available EE.…”
Section: Introductionmentioning
confidence: 99%